The Effect of Corporate Governance on Cash Holdings - Darma, Nasya Saniyah; Lukviarman, Niki; Setiany, Erna (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
Purpose: This study aims to tests the effect of corporate governance on cash holdings empirically. This study proxies corporate governance into four proxies: family ownership, institutional ownership, size of the board of commissioners, and proportion of independent commissioners. In addition, this research uses five control variables, namely, bank relationship, company size, leverage, return on assets, and cash flows.Method: The samples were chosen based on the purposive sampling technique from consumer goods companies listed in the Indonesian Stock Exchange during 2015-2019, with 77 firm years. In order to test hypotheses, this study performed multiple regression analysis.Finding: The results showed that board independence negatively affect cash holdings, while family ownership, institutional ownership, and board size have not.Novelty: This study extends the limited previous research on the relationship between corporate governance and cash holdings, especially in the consumer goods industry sector listed on the Indonesia Stock Exchange for the period 2015-2019.